1989
DOI: 10.1002/1097-0142(19891101)64:9<1769::aid-cncr2820640902>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Phase II randomized clinical trial of LC9018 concurrently used with radiation in the treatment of carcinoma of the uterine cervix. Its effect on tumor reduction and histology

Abstract: The clinical efficacy of LC9018, a biological response modifier prepared from heat-killed Lactobacillus casei YTT9018, used in combination with radiation was studied in a randomized controlled trial on 61 patients with carcinoma of the uterine cervix of Stage IIB or III. The combination therapy with LC9018 demonstrated a significant effect on tumor reduction, compared with radiation therapy alone, at the cumulative doses of 15-Gy and 30-Gy external irradiation (P less than 0.05). Histologic study confirmed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…1980). Moreover, use of LAB in patients with cervical cancer demonstrated a clear effect on tumour reduction compared with radiotherapy alone (Okawa et al . 1989).…”
Section: Resultsmentioning
confidence: 99%
“…1980). Moreover, use of LAB in patients with cervical cancer demonstrated a clear effect on tumour reduction compared with radiotherapy alone (Okawa et al . 1989).…”
Section: Resultsmentioning
confidence: 99%
“…4, 5), suggesting that inhibition of the growth of pathogenic bacteria resulted in the suppression of subsequent infection-induced inflammatory responses. L. casei Shirota reportedly exerts antitumor (4,32,45,54) and antimicrobial (47,52,53,70) activities in clinical and preclinical studies. Furthermore, nonspecific augmentation of components of the innate immune system, such as macrophages (34,47,63) and natural killer cells (33), has been thought to play important roles in these activities.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some early reports have suggested that heat-killed Lactobacillus casei Shirota could be useful in the treatment of carcinoma of the uterine cervix (44, 45) and secondary to lung cancer (46). In one preclinical study, viable L. casei was found to be more effective than heat-killed L. casei in the prevention of secondary tumours in preimmunized mice (47).…”
Section: Clinical Benefits Of Probiotics – Is Viability Essential?mentioning
confidence: 99%